2016
DOI: 10.1002/hyp.10868
|View full text |Cite
|
Sign up to set email alerts
|

Submarine groundwater discharge revealed by aerial thermal infrared imagery: a case study on Jeju Island, Korea

Abstract: Submarine groundwater discharge (SGD) is a global phenomenon that carries large volumes of groundwater and dissolved chemical species such as nutrient, metals, and organic compounds to coastal zones. We report the influence of SGD on the coastal waters of Jeju Island, Korea, using high‐resolution aerial thermal infrared (TIR) mapping techniques and field investigations. An aircraft‐based system was implemented using a cost‐effective TIR camera for aerial TIR mapping. Ground‐based calibrations and system integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…The SST maps also illustrate that, ideally, radon models for time‐series stations should incorporate a new area and volume estimate for each analysis cycle because the plumes are dynamic. Although challenging, one could conceivably determine areas and volumes for each analysis cycle by using distributed temperature sensors or through continuous TIR data collection by a perched camera from a high vantage point, manned flights, or drones (e.g., Lee et al ; Kennedy ). Our TIR data also generally had a much higher resolution (3.2 m) than our radon survey data (1 to 100 m).…”
Section: Discussionmentioning
confidence: 99%
“…The SST maps also illustrate that, ideally, radon models for time‐series stations should incorporate a new area and volume estimate for each analysis cycle because the plumes are dynamic. Although challenging, one could conceivably determine areas and volumes for each analysis cycle by using distributed temperature sensors or through continuous TIR data collection by a perched camera from a high vantage point, manned flights, or drones (e.g., Lee et al ; Kennedy ). Our TIR data also generally had a much higher resolution (3.2 m) than our radon survey data (1 to 100 m).…”
Section: Discussionmentioning
confidence: 99%
“…The reason that the amount of SGD in Bangdu Bay is greater than in other typical continental margins is the inclusion of recirculated SGD across the sediment–seawater interface. The SGD in Gongcheonpo Beach is known to mainly consist of SFGD (E. Lee, Kang, et al, ). Lastly, Kimnyung Bay is made of a harbour that is relatively deeper than other typical beach or bay.…”
Section: Resultsmentioning
confidence: 99%
“…Airborne TIR remote sensing has been used in an attempt to show the spatial variability of SGD at higher spatial resolutions than space‐borne TIR imagery is capable of demonstrating (Bejannin, van Beek, Stieglitz, Souhaut, & Tamborski, ; Kelly, Glenn, & Lucey, ; Mejías et al, ; Mulligan & Charette, ; Tamborski et al, ). Our research team has previously presented the possibility of detecting SGD around Jeju Island using airborne TIR imagery (E. Lee, Kang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have utilized a variety of remote sensing platforms to investigate groundwater discharge patterns and rates under different hydrogeologic regimes, including point‐source (Kelly et al ., ) and diffuse SGD (Lee et al ., ) in a volcanic environment (Hawaii and Jeju Island, Korea, respectively), diffuse SGD from a permeable unconfined coastal aquifer (Long Island Sound, NY; Tamborski et al ., ), and from freshwater springs (Prince Edward Island, Canada; Danielescu et al ., ). To utilize TIR remote sensing techniques for hydrologic investigations, it is necessary that a wide variety of hydrologic environments under a range of environmental conditions be thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . () found that coastal sea‐surface temperatures (measured by airborne TIR remote sensing) changed with temporally variable fresh SGD rates, in response to a tidally modulated hydraulic gradient. Ground‐based TIR imagery can be used to detect small‐scale groundwater discharge springs that are not readily apparent to the naked eye, even in porous systems where groundwater seepage is expected to be primarily diffuse (Röper, Greskowiak, & Massmann, ).…”
Section: Introductionmentioning
confidence: 99%